George Pólya Winners (The College mathematics journal, 2006)
Professor Frederickson has done research in the area of the design and analysis of algorithms, with major contributions to approximation algorithms for NP-hard problems, graph and network algorithms, and data structures. (What a treat it is to read Euler's own words on the matter.) Hopkins and Wilson take us back to the founding of the city of Königsberg in 1254, then gently help us relive history through their translations set in rich historical context, of the correspondence between Euler and other mathematicians concerning this interesting puzzle.